Impact of digital readiness factors on implementation of Industry 4.0 tools for the manufacturing industries of Karnataka - An Analytical Study - Samapika Satapathy; Dr. M A Rasheed; Dr. Santanu kumar Das (Srusti Management Review, 2025)
Implementation of digital technologies brings a significant industrial revolution in manufacturing processes, often referred to as Industry 4.0. However, manufacturing industries in Karnataka face numerous challenges in adopting these advanced technologies. The manufacturing industry needs to constantly evolve itself with various smart manufacturing techniques. They need to be digitally equipped to adapt to these advanced technologies. The digital readiness of these manufacturing industries plays an important role in the digital implementation and adaptation of advanced technologies in the manufacturing process. Various pieces of literature have been reviewed to understand the influential factors i.e Digital operational efficiency, Supply chain integration and logistics, Product quality and customization, Technological enablers, Skill Competencies of employees, Financial Support, Cyber security, Product Innovation Development and Process innovation Development, impacting the digital readiness of the organization towards implementation. A survey through a questionnaire was conducted to collect data from 50 manufacturing industries in the Karnataka, India. These industries were working towards achieving digital implementation. The primary data was collected through the survey and it was supplemented by the secondary data sources such as data from books, research papers, journals, annual reports, and websites etc. This consolidated data were analysed using Minitab (V_17) software, using descriptive statistics, Validity and reliability analysis, correlation analysis, and linear-regression analysis. The findings reveal moderate to strong correlations between various digital readiness constructs and the digital implementation of the manufacturing industries. Based on this study, Karnataka’s manufacturing industries demonstrate a high level of readiness and capacity for digital transformation, suggesting that broad-based initiatives could effectively support their adoption of Industry 4.0 technologies. This study provides actionable insights for policymakers and business leaders to facilitate the successful adoption of Industry 4.0 tools.